Testing the extreme male hypothesis in the valproate mouse model; sex-specific effects on plasma testosterone levels and tyrosine hydroxylase expression in the anteroventral periventricular nucleus, but not on parental behavior - Grgurevic, Neza (Frontiers in Behavioral Neuroscience, 2023)
Introduction Autism is a neurodevelopmental disorder with a strong male bias in prevalence and severity. The extreme male hypothesis proposed that autism is a manifestation of extreme male traits as evidenced by increased masculine behaviors, hypermasculinization of some brain regions, and alterations in androgen metabolism. In the present study, the extreme male hypothesis was tested in the valproate (VPA) mouse model. Methods Females of the C57BL/6JOlaHsd mouse strain were treated with 500 mg/kg VPA on gestational day 12. Offspring of both sexes were tested at 3 to 4 months of age in the elevated plus maze (EPM), open field, sociability tests, and for parental behavior. After sacrifice at 5 to 6 months of age, plasma testosterone was measured in males, while the brains of both sexes were examined for tyrosine hydroxylase (TH) expression in the anteroventral periventricular nucleus (AVPV). Results VPA treatment significantly increased plasma testosterone levels and decreased AVPV TH expression in males, whereas the expression of TH in females remained at the same level. In parental behavior test none of the pup-oriented behavior was affected by VPA treatment in both sexes, the exception was nest quality which was lower after VPA exposure in males, but not in females. Discussion Our results suggest a hypermasculinizing effect of VPA that occurred specifically in males but not in females, and this effect could be related to changes in androgen physiology. Nevertheless, a generalized interpretation of the extreme male hypothesis on brain and behavior should be avoided due to the complex effects of VPA.